Formation of p62‐positive inclusion body is associated with macrophage polarization in non‐alcoholic fatty liver disease. Issue 9 (10th April 2018) - Fukushima, Hirofumi; Yamashina, Shunhei; Arakawa, Atsushi; Taniguchi, Gentaro; Aoyama, Tomonori; Uchiyama, Akira; Kon, Kazuyoshi; Ikejima, Kenichi; Watanabe, Sumio
Abstract : Aim: Hepatic inclusion composed of autophagy‐specific substrate p62 is one of the histological features of non‐alcoholic fatty liver disease (NAFLD) and can be a precursor to hepatic carcinogenesis. The expression of p62 was enhanced by not only autophagic dysfunction but also oxidative stress and inflammation. M1/M2 phenotypic balance of macrophages plays a pivotal role in the progression of NAFLD. We evaluated the correlation between macrophage polarization and the formation of p62 aggregation in NAFLD. Methods: Liver biopsy specimens from NAFLD patients were analyzed by immunohistochemical staining for M1 macrophage marker CD11c, M2 macrophage marker CD163, and p62/SQSTM1 (p62). The histological severity of NAFLD is assessed by a NAFLD activity score (NAS). The number of autophagic vesicles in hepatocytes was visualized and counted by using transmission electron microscopy. Results: The aggregation of p62 was undetectable in control, whereas hepatocytes with p62 aggregation were observed in approximately 88% of NAFLD specimens. The number of hepatocytes with p62 aggregation was positively correlated with the number of autophagic vesicles, serum alanine aminotransferase, NAS, fibrosis, and the number of CD11c‐positive cells, but not CD163‐positive cells. Assembly of CD11c‐positive cells was observed around hepatocytes with p62 aggregation. The ratio of CD11c/CD163‐positive macrophages was significantly associated with the formation of p62 aggregation. Conclusions: These findings indicate that chronic inflammation by M1‐polarization of macrophages contributes to the disease progression from simple steatosis to non‐alcoholic steatohepatitis in concert with autophagic dysfunction.